Distal humerus nonunion: evaluation and management. Issue 5 (1st May 2020) - Vauclair, Frédéric; Goetti, Patrick; Nguyen, Ngoc Tram V.; Sanchez-Sotelo, Joaquin
Abstract : Despite recent improvements in surgical implants and techniques, distal humerus nonunion does occur between 8% and 25% of the time. Careful identification and improvement of any modifiable risk factors such as smoking, metabolic disorders, immunosuppressant medications, poor nutritional status and infection is mandatory. A recent computed tomography scan is paramount to determine the nonunion pattern, assess residual bone stock, identify previously placed hardware, and determine whether there is evidence of osteoarthritis or malunion of the articular surface. Internal fixation is the treatment of choice in the majority of patients presenting with reasonable bone stock and preserved articular cartilage; total elbow arthroplasty is an appealing alternative for elbows with severe destruction of the articular cartilage or severe bone loss at the articular segment, especially in older, female patients. Internal fixation requires not only achieving a stable fixation, but also releasing associated elbow contractures and the liberal use of bone graft or substitutes. Although reported union rates after internal fixation of distal humerus nonunions are excellent (over 95%), the complication rate remains very high, and unsatisfactory results do occur. Cite this article: EFORT Open Rev 2020;5:289-298. DOI: 10.1302/2058-5241.5.190050